2020
DOI: 10.1021/acsapm.0c00828
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Porous Poly(dimethylsiloxane) (PDMS) Adhesives

Abstract: In this study, we propose a simple low-cost emulsion-based method to fabricate porous poly­(dimethylsiloxane) (PDMS) adhesive films, with a focus on their possible application as wound dressings. In this method, water is added to PDMS to form an emulsion. On film-casting the emulsion and curing it at 120 °C, evaporation of water droplets and PDMS cross-linking result in randomly distributed pores/voids in the bulk of the PDMS film. A huge advantage of the proposed method over conventional approaches is its sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…Very recently, Mohania et al used an emulsion based fabrication method, using water as a porogen, to fabricate porous PDMS adhesive films . The authors demonstrated that generation of bulk porosity resulted in increased surface roughness, which hindered in proper contact of the adhesive film with the substrate and hence reduced the adhesion (see Figure a,b).…”
Section: Subsurface Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Mohania et al used an emulsion based fabrication method, using water as a porogen, to fabricate porous PDMS adhesive films . The authors demonstrated that generation of bulk porosity resulted in increased surface roughness, which hindered in proper contact of the adhesive film with the substrate and hence reduced the adhesion (see Figure a,b).…”
Section: Subsurface Structuresmentioning
confidence: 99%
“…(d) Scanning electron micrograph of PDMS foam, (e) close-up image of (left) sugar cube (template) and (right) PDMS foam adhesive cube, and (f) load vs displacement data for the adhesive foam and film-terminated adhesive foam. Parts a–c have been reprinted with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Subsurface Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Many materials should be coated with a thin protective layer to provide an adequate surface finish and stability in harsh environments [1][2][3][4][5]. A variety of techniques have been proposed, and a few have also been commercialized [6][7][8][9][10]. One technique for depositing compact and hydrophobic films similar to polydimethylsiloxane (PDMS) is plasma polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative occlusion material, the ML elastomer should also have good mechanics and biological performance, which suggests that the employed flexible matrix for the ML elastomer is of great importance. Polydimethylsiloxane (PDMS) is frequently used as the matrix for ML powders because of its high optical transparency, efficient stress transfer ability, and easy fabrication. , Moreover, PDMS shows excellent biocompatibility and permeability, high-temperature resistance, and natural hydrophobicity. Therefore, the elastomer composed of ML powders and PDMS matrices is promising to replace the existing occlusal materials to possess better overall performance and visualized occlusal inspection.…”
Section: Introductionmentioning
confidence: 99%